Relationships between carcass characteristics, meat quality, age and sex of free-ranging Alaskan reindeer: a pilot study - Renecker, Teresa A.; Renecker, Lyle A.; Mallory, Frank F. (Rangifer, 2005)
Twenty-four reindeer (Rangifer tarandus) carcasses from male and female animals that ranged in age from calves to adults were purchased from Bering Sea Reindeer Products (BSRP), Nunivak Island, Alaska, USA. Preslaughter and abattoir procedures were observed and evaluated. Carcasses were split in half, weighed, and broke into wholesale primal cuts of chuck, rib, loin, and hindquarter. Each primal cut was weighed, boxed, and frozen. Each half carcass of primal cuts was later dissected into lean tissue, bone, and the three compartments of fat: subcutaneous, intermuscular, and peritoneal. A portion of the loin was collected from each animal in order to obtain data on pH and shear force. Sensory panel analysis was performed on loin steaks. Due to management and environmental effects, pH values were high and the meat was dark in colour. Carcasses from adult male reindeer contained significantly lower levels of fat than carcasses of adult females. Data indicated that yearling reindeer are of greatest economic value for meat production.